2016
DOI: 10.1089/scd.2016.0212
|View full text |Cite
|
Sign up to set email alerts
|

Human Embryos Created by Embryo Splitting Secrete Significantly Lower Levels of miRNA-30c

Abstract: Studies reporting term pregnancy and the production of genetically identical offspring from isolated blastomeres of early stage embryos have been carried out in small and large animals. However, very little is known about the effects of embryo splitting on the development and reproductive competency of human embryos. In this study, we investigated the effects of embryo splitting on profile of microRNAs (miRNAs) detected in their spent blastocyst medium (SBM) by comparative analysis of miRNA profiles in SBM of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The same group subsequently compared the profiles of 377 miR sequences in spent media from "twin" human blastocysts created by artificial embryo splitting at the cleavage stage with that of control blastocysts that produced healthy pregnancies [24]. They found 59 miRs secreted by control blastocysts and 48 miRs by twin embryos of which, only 22 were shared.…”
Section: Embryo-derived Evs Exert Extra-and Intra-embryonic Effectsmentioning
confidence: 99%
“…The same group subsequently compared the profiles of 377 miR sequences in spent media from "twin" human blastocysts created by artificial embryo splitting at the cleavage stage with that of control blastocysts that produced healthy pregnancies [24]. They found 59 miRs secreted by control blastocysts and 48 miRs by twin embryos of which, only 22 were shared.…”
Section: Embryo-derived Evs Exert Extra-and Intra-embryonic Effectsmentioning
confidence: 99%
“…The delivery of miR-30c mimics to the MDBKs led to reduced cell proliferation and an arrest at G1 stage, while the delivery of miR-30c inhibitors resulted in the opposite effects, as expected. Previous studies on human embryos suggested that miR-30c can serve as a potential marker of blastocyst implantation potential (Capalbo et al, 2016; Noli et al, 2016). This is not surprising because although miR-30c is highly conserved between different species, it has been shown to act differently among different species.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the EVs, miRNAs have also been identified in culture media of human blastocysts and are detected in biopsied trophectoderm cells suggesting they are released from blastocysts [20][21][22][23][24]. While a formal proof that these miRNAs are EV-derived is yet awaited, since exosomes are enriched with miRNAs, it can be presumed that these blastocysts derived miRs could be secreted via MVs.…”
Section: Embryo-derived Extracellular Vesicles Aid In Embryo Growth Amentioning
confidence: 99%